Survived so what?: identifying priorities for research with children and families post-paediatric intensive care unit - Manning, Joseph C.; Hemingway, Pippa; Redsell, Sarah A. (Wiley, 2018)
The involvement of patients and the public in the development, implementation and evaluation of health care services and research is recognized to have tangible benefits in relation to effectiveness and credibility. However, despite >96% of children and young people surviving critical illness or injury, there is a paucity of published reports demonstrating their contribution to informing the priorities for aftercare services and outcomes research. We aimed to identify the service and research priorities for Paediatric Intensive Care Unit survivors with children and young people, their families and other stakeholders. We conducted a face‐to‐face, multiple‐stakeholder consultation event, held in the Midlands (UK), to provide opportunities for experiences, views and priorities to be elicited. Data were gathered using write/draw and tell and focus group approaches. An inductive content analytical approach was used to categorize and conceptualize feedback. A total of 26 individuals attended the consultation exercise, including children and young people who were critical care survivors; their siblings; parents and carers; health professionals; academics; commissioners; and service managers. Consultation findings indicated that future services, interventions and research must be holistic and family‐centred. Children and young people advisors reported priorities that focused on longer‐term outcomes, whereas adult advisors identified priorities that mapped against the pathways of care. Specific priorities included developing and testing interventions that address unmet communication and information needs. Furthermore, initiatives to optimize the lives and longer‐term functional and psycho‐social outcomes of Paediatric Intensive Care Unit survivors were identified. This consultation exercise provides further evidence of the value of meaningful patient and public involvement in identifying the priorities for research and services for Paediatric Intensive Care Unit survivors and illuminates differences in proposed priorities between children, young people and adult advisors.